Pemberdayaan Kader Aisyiyah Pimpinan Ranting Aisyiyah Kedungwuluh Kidul Kecamatan Patikraja Melalui Pelatihan Budidaya Cacing Tanah: Empowerment of Aisyiyah Cadres, Aisyiyah Branch Leadership, Kedungwuluh Kidul, Patikraja District, Through Earthworm Cultivation Training - Purnawanto, Agus Mulyadi; Shofiyani, Anis; Pramono, Hadi (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
The Aisyiyah Branch Leadership (ABL) of Kedungwuluh Kidul, Patikraja District, is part of the Aisyiyah organization that focuses on women's empowerment. Kedungwuluh Kidul has abundant potential for natural resources, including organic waste from households and agriculture. This waste can be used to cultivate earthworms, which produce high-value products: vermicompost and the worms themselves. However, members of the ABL Kedungwuluh Kidul do not yet have the knowledge and technical skills related to earthworm cultivation and its business processes, so planned educational efforts are needed to optimize local potential. Therefore, through community service activities, the knowledge, abilities, and skills of the Aisyiyah Branch Leadership cadres of Kedungwuluh Kidul, Patikraja District can be improved. Community service activities are carried out through a theoretical approach (lectures), practice (training), and mentoring (evaluation). The training results showed that there was an increase in partners' understanding and skills on the benefits of vermicompost, earthworm cultivation techniques, and business prospects for earthworms and vermicompost, from the initial 70% of participants did not understand and even 30% did not understand, to 65% of participants who understood, many understood, and 35% understood. Not a single participant did not understand.